Adjunctive hyperbaric oxygen therapy with reconstruction of lower eyelid for basal cell carcinoma: A case series. (February 2023) - Oley, Mendy Hatibie; Oley, Maximillian Christian; Gunawan, Deborah Florencia; Rangan, Andi A.; Wagiu, Angelica Maurene Joicetine; Faruk, Muhammad
Abstract: Introduction: Basal cell carcinoma (BCC) is among the most widespread non-melanoma skin cancers, with an incidence of around 80 % worldwide. Surgery is the main therapy of choice. High-pressure oxygen is used in hyperbaric oxygen therapy (HBO) to treat hypoxic tissue conditions. By using this technique, the tissue oxygen tensions increase. This is used to treat a wide range of diseases and disorders brought on by hypoxic states, circulation issues, inadequate tissue oxygenation due to vascular damage, tissue damage from infections or accidents, and impairment of tissue healing. Cases presentation: This paper presents five cases of HBO used in the healing BCC surgery. All patients underwent wide and deep excisions with eight adjunctive sessions of HBO therapy. Clinical discussion: The five cases of post-surgery wound healing improved significantly with HBO. Conclusion: BCC is a condition that is frequently identified in the outpatient department. Prerequisites for a better prognosis include early diagnosis based on sound information and prompt, structured, and sufficient therapy. Our study reveals the benefit of HBO in increasing wound healing and preventing complications after surgery for BCC. Highlights: Surgery is the main therapy of choice in basal cell carcinoma. Hyperbaric oxygen (HBO) therapy is typically used as an additional treatment. Five cases of post-surgery wound healing improved significantly with HBO. Follow-up at 6 months to 1 year after the procedure showed no recurrence.